Beyond Political Theology and its Liquidation: From Theopolitical Monotheism to Trinitarianism - Mrówczyński-Van Allen, Artur (Modern theology, 2017)
One of the central theological challenges facing Erik Peterson was to help the mid-twentieth century Catholic Church define its relationship with the wider world. He responded by advancing a distinctive understanding of the 'polis.' In this essay, I critically analyze Peterson's central and perhaps best known proposal about how the Church ought to negotiate the modern world - encapsulated in his expression, the 'liquidation of political theology.' I contend that Peterson's proposal is not congruent with a right understanding of patristic trinitarian monarchy, although a view that stands in sharp contrast to that of Carl Schmitt. Notwithstanding the effectiveness of Peterson's critique of Schmitt's political theology, I argue that Peterson nonetheless fails in his exposition of the thought of Gregory of Nazianzus and therefore in his interpretation of the role of the Church in what we have learned to call the 'political' and the 'social.' I conclude by outlining several ways that the Church today might take up the challenge of regaining a truly political thought, a new ekklesioteia, nourished by the monarchy of the triune God.